Effects of eccentric and concentric isokinetic bench press training on dynamic strength, isometric force production and triceps brachii cross-sectional area - Wanttaja, Ryan (2020)
Background. Engaging in resistance training programmes is an integral part of the physical preparation process for athletes. The neural and morphological mechanisms underpinning eccentric contractions are notably different from concentric and isometric contractions and remain less understood. Performing compound movements with an eccentric load greater than the individual’s maximum strength capacity has become a popular interest in the quest to understanding how the neuromuscular system adapts acutely and chronically. Reversible physiological adaptations occur if there is a short-term insufficient training stimulus and thus, meticulous physical preparation planning is essential. The purpose of this study was to investigate the differences in strength and CSA between groups, and to compare the changes that occurred as a result of training between- and within-groups. Methods. Subjects (n = 17) were randomly assigned to an eccentric overload (n = 9) or concentric (n = 8) training group. The males were physically fit and had engaged in recreational resistance training prior to the study. Training took place twice per week on non-consecutive days for a duration of 10 weeks, after which, five weeks of detraining. Contractions were performed in isolation with the volume and intensity ranging between three to four sets and repetitions. Maximum dynamic strength was found using a smith machine bench press in accordance to 1RM testing procedures; maximum isometric strength was performed on a bench press set-up with an immovable bar. Triceps brachii CSA was measured via panoramic ultrasonography. Strength and CSA was measured three times: pre-test, post-test and after detraining. Results. There was a significant, within-group difference in absolute 1RM bench press strength for the eccentric training group (p < .05) from pre- to post-test, but not for the concentric group. Isometric strength increased to a greater extent for the concentric group, however, the mean change between groups was not significant (p > .05). A greater mean increase in combined triceps brachii CSA was found for the eccentric group which remained above baseline values after detraining unlike the concentric group. There was however a strong correlation (r = 0.74) between the change in combined CSA and change in isometric strength for the concentric group as a result of training. Conclusion. This research contributes to an ongoing research interest of eccentric resistance training with eccentric overload, in particular, the upper extremity musculature. Each contraction type performed in isolation was not significantly different from one another, however, performing these can elicit significant changes in antagonist muscle cross-sectional area, dynamic and isometric strength with training.